Multiple Assessment Methods Towards the Improvement of Students’ English Language Learning - Sugiono, Sugiono (International Journal of English Education and Linguistics (IJoEEL), 2021)
The study explores the perspective of multiple assessment methods and possibility of applying it in English language learning. Assessment of English language learning needs to consider the philosophical perspective of progressive education. Assessment in progressive notions of education is primarily used to nurture and develop individual students’ capacity and range of talents. Likewise, the perspective of the 2013 National Curriculum demands students’ real performance on relevant tasks. The study notes that an assessment process refers to implementing multiple methods or a range of strategies to make decisions regarding instruction and gathering information about students’ performance and behaviour, diagnoses students’ problems, monitors their progress and gives feedback for improvement. Rather than a single method of assessment, multiple assessment methods are more beneficial to help the teacher triangulate the evidence for a complete picture of student comprehension and understanding. Every method of assessment has weaknesses, and hence, by using multiple assessment methods, the strengths of one particular method can overcome the problematic weaknesses of another.